Impact of a heart failure multidisciplinary clinic on the reduction of healthcare-related events and costs: the GEstIC study - Rego, Rita; Pereira, Nuno; Pinto, António; Pereira, Sofia; Marques, Irene (Frontiers in Cardiovascular Medicine, 2023)
Heart failure (HF) is the leading cause of hospitalization in the elderly population. HF patients often experience an impaired functional status, diminished quality of life, and poor survival, representing a significant burden on public health expenditures. Minimizing the need for HF patients to resort to public health systems by reducing hospitalizations and urgent visits would significantly reduce the costs to public health institutions. Previous studies showed that admitting HF patients to multidisciplinary HF clinics improved health indicators, reduced hospitalizations, and, consequently, hospital costs. However, in Portugal, most HF patients are still not managed in multidisciplinary integrated care programs. This real-world study demonstrates that the implementation of a multidisciplinary clinic for the care of HF patients significantly reduces the number of HF events (hospitalizations and urgent visits) and related costs in the population of a single hospital. The resulting savings to the healthcare system were more than €1,500,000 in one year of patients' follow-up. It also validates the feasibility of implementing a multidisciplinary HF clinic in a public hospital setting. If a similar model were replicated nationally, the health and financial benefits would be remarkable.